PEMANFAATAN MUSEUM SEBAGAI OBJEK WISATA EDUKASI - Danang Prasetyo; Toba Sastrawan Manik; Dwi Riyanti (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2021)
The purpose of this study is to describe or strengthen the function of the museum as a means of education outside the classroom as part of the co-curricular education program. This program is often referred to as an educational tourism activity. This research is a descriptive qualitative research that uses data collection methods through literature study using various sources such as books, journal articles, and news sources that support the research. Data collection, data processing, and data analysis were carried out from September 2020 to January 2021. The conclusions of this study are: (1) museums have an educational function that must be elaborated and used as a source, media, and place of learning as part of educational co-curricular program. Museums provide open communication about ideas, concepts, information involving exploration and discovery. Museum is a place of learning for 3A (the authentic, the aesthetic, and the accessible). (2) it is necessary to increase the role, quality and professionalism of the teaching staff so that the museum can function effectively and improve the quality of education. (3) it is necessary to have the role of museum managers and related policy makers to optimize the quality and accessibility so that the museum is easily accessible to tourists and is open to educational programs. In addition, innovation is needed in managing museum tourism so that it can attract tourists. Thus, synergy is needed between museum managers as providers and formal educational institutions as users in the use of museums in educational functions.Keywords: Museums, Object Tourism, Education Tourism